2009
DOI: 10.1007/s00415-009-5087-5
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial lipomas: clinical appearances on neuroimaging and clinical significance

Abstract: Intracranial lipomas are rare congenital malformations which are neither hematomas nor true neoplasms. They result from the abnormal persistence and maldifferentiation of the meninx primitiva. The majority of such lesions occur near the midline. Around 55% of intracranial lipomas are associated with brain malformations of varying severity. Although they are usually an incidental finding, symptomatic intracranial lipomas are sometimes observed. Surgical excision may result in high morbidity and mortality due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 4 publications
1
54
0
11
Order By: Relevance
“…These benign lesions are thought to arise from differentiation of the meninx primitiva, a mesenchymal derivative of neural crest, to lipoma tissue. The vast majority of these types of lesions occur near the midline [1] . More than 50% have been reported to be associated with congenital brain malformations such as agenesis or hypoplasia of the corpus callosum [2] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These benign lesions are thought to arise from differentiation of the meninx primitiva, a mesenchymal derivative of neural crest, to lipoma tissue. The vast majority of these types of lesions occur near the midline [1] . More than 50% have been reported to be associated with congenital brain malformations such as agenesis or hypoplasia of the corpus callosum [2] .…”
Section: Discussionmentioning
confidence: 99%
“…More than 50% have been reported to be associated with congenital brain malformations such as agenesis or hypoplasia of the corpus callosum [2] . Others include the absence of the septum pellucidum, cranium bifidum, spina bifida, myelomeningocele, hypoplasia of the vermis and malformation of the cortex [1] . In this case, we found that the septum pallucidum was absent [ Figure 4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracranial lipomas affect more frequently females than males (2:1) [3]. Most lipomas occur at or near the midline, and only 9-12% are found in the CPA [4,6,7]. In symptomatic cases lipomas of the CPA can cause vertigo, dizziness, tinnitus, and loss of hearing [3,4,8].…”
Section: Introductionmentioning
confidence: 99%
“…They are rare congenital abnormalities, which are not true neoplasms. They originate from the primitive meninx and contain adipose tissue [3,4,5,6]. Intracranial lipomas affect more frequently females than males (2:1) [3].…”
Section: Introductionmentioning
confidence: 99%